Assessing the Impact of Erosion and Farming Practices on the Spatial Distribution of Topsoil Characteristics in a Sloping Vineyard Using an Open-source QGIS Software - Ha Nhung, Pham Thi; Viet, Nguyen Quoc (VNU Journal of Science: Earth and Environmental Sciences, 2023)
Erosion is one of the major threats that negatively affect agricultural soils. Several studies indicated that sloping vineyards are prone to soil erosion due to the soil management method. This study was conducted in a sloping vineyard planted in 2019 (with a slope of 10 0 and a slope length of 38 m) in Thu Cuc commune, Tan Son district, Phu Tho province, Vietnam. The main objective of the study is to evaluate soil characteristics (pH, particle-size distribution, organic matter, cation exchange capacity (CEC), N, P, and K macronutrients) related to terrain morphology, soil erosion, and farming practices. The open-source QGIS software was used to evaluate the spatial distribution of the soil characteristics. We found that the organic matter content, CEC, and clay content in the soils taken at the footslope zones were higher than those at the top of the hill as a result of soil erosion. In contrast, higher contents of K and silt were observed at the top of the hill compared to the footslope, indicating an unapparent impact of soil erosion on these two factors in the studied vineyard. Phosphorus was evenly distributed throughout the plot and influenced by the soil characteristics. Indeed, a strong correlation between total P content and soil pH, organic matter, and silt content was revealed in our study. On the other hand, cultivation practices exerted a significant impact on the prevailing accumulation of soil organic matter, CEC, total N, and clay particle size at the lower part of the vine rows following the horizontal flow. The vine rows were planted along the contour lines rather than the dominant slope of the vineyard can explain this tendency. In addition, no cover crops sown between the vine rows probably resulted in intense soil erosion at the steepest part of the terrain. Overall, the terrain morphology and farming practices played an essential role in the spatial distribution of soil characteristics. Therefore, integrating geographic information systems into building a digital database and predicting the spatial distribution of soil parameters is necessary to perform soil quality monitoring and serve sustainable land management.